Current status and outlook on the clinical translation of biodegradable metals - Han, H; Loffredo, S; Jun, I; Edwards, J; Kim, Y-C; Seok, H-K; Witte, F; Mantovani, D; Glyn-Jones, S (Elsevier, 2018)
During the last decade, translational research on biodegradable metallic materials has shown the feasibility of these novel materials for use in the fields of cardiology and orthopedics. Implants prepared with biodegradable metals are significantly stronger than their polymer counterparts, and there is now convincing evidence demonstrating that these materials fully biodegrade in vivo, thus reducing the need for secondary surgery. Clinical trials of such novel materials show significant potential, with the prospect of a paradigm shift in the way musculoskeletal and cardiovascular conditions are treated. This work provides an overview of the rapidly advancing technology of biodegradable metals, as well as defining some challenges in the application of these new biodegradable materials in the medical field.